An Analytical Study of Science Students’ Attitudes Toward Environmental Conservation Issues and Actions - Lalu Kesumajayadi; Salman Al Farisi; Muhamad Sumarlin; I Gde Adi Suryawan Wangiyana (Faculty of Engineering and Applied Science, 2025)
This study aims to analyze science students’ attitudes toward environmental conservation issues and actions, with a focus on understanding personal commitment, emotional engagement, conservative values, and appreciation for environmental education. Employing a mixed-methods approach, quantitative data were obtained from 43 students through a five-point Likert-scale attitude questionnaire, while qualitative data were collected through in-depth interviews with six selected respondents. Quantitative analysis revealed an average attitude score of 24.56, categorized as